The difference between oats and beta-glucan extract intake in the management of HbA1c, fasting glucose and insulin sensitivity: a meta-analysis of randomized controlled trials. Issue 3 (3rd February 2016) - He, Li-xia; Zhao, Jian; Huang, Yuan-sheng; Li, Yong
Abstract : This study aims to assess the different effects between oats (whole and bran) and beta-glucan extract intake on glycemic control and insulin sensitivity. Abstract : Increasing oats and beta-glucan extract intake has been associated with improved glycemic control, which is associated with the reduction in the development of diabetes. This study aims to assess the different effects between oat (whole and bran) and beta-glucan extract intake on glycemic control and insulin sensitivity. PubMed, Embase, Medline, The Cochrane Library, CINAHL and Web of Science were searched up to February 2014. We included randomized controlled trials with interventions that lasted at least four weeks that compared oats and beta-glucan (extracted from oats or other sources) intake with a control. A total of 1351 articles were screened for eligibility, and relevant data were extracted from 18 studies ( n = 1024). Oat product dose ranged from 20 g d −1 to 136 g d −1, and beta-glucan extract dose ranged from 3 g d −1 to 10 g d −1 . Compared with the control, oat intake resulted in a greater decrease in fasting glucose and insulin of subjects ( P < 0.05), but beta-glucan extract intake did not. Furthermore, oat intake resulted in a greater decrease in glycosylated hemoglobin (HbA1c) ( P < 0.001, I 2 = 0%) and fasting glucose ( P < 0.001, I 2 = 68%) after removing one study using a concentrate and a different design and fasting insulin of type 2 diabetes (T2D) ( P < 0.001, I 2 = 0%). The intake of oats and beta-glucan extracted from oats were effective in decreasing fasting glucose ( P = 0.007, I 2 = 91%) and fasting insulin of T2D ( P < 0.001, I 2 = 0%) and tented to lower HbA1c ( P = 0.09, I 2 = 92%). Higher consumption of whole oats and oat bran, but not oat or barley beta-glucan extracts, are associated with lower HbA1c, fasting glucose and fasting insulin of T2D, hyperlipidaemic and overweight subjects, especially people with T2D, which supports the need for clinical trials to evaluate the potential role of oats in approaching to the management of glycemic control and insulin sensitivity of diabetes or metabolic syndrome subjects.